Kunci Kinerja Perusahaan Energi: Good Corporate Governance, Ukuran Perusahaan, dan Leverage - Kustiningsih; Sulistyo; Irma Tyasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research was conducted using quantitative methods, specifically observational analytical studies aimed at analyzing the correlation between variables, namely good corporate governance represented by independent commissioners, managerial ownership, institutional ownership, audit committees, firm size, and leverage on company performance assessed by Return On Assets (ROA) as the dependent variable. This study focuses on 87 energy companies listed on the Indonesia Stock Exchange (BEI) as the population, and by using purposive sampling technique, 56 samples were obtained. The data used is sourced from the annual reports of energy companies from 2021 to 2024. The results of this study indicate that institutional ownership and firm size affect company performance (ROA), while independent commissioners, managerial ownership, audit committees, and leverage do not affect company performance (ROA).